Molecular identification of the fish fauna from the pantanal flood plain area in Brazil - Shimabukuro-Dias, Cristiane Kioko [UNESP]; Costa Silva, Guilherme Jose da [UNESP]; Ashikaga, Fernando Yuldi [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Taylor & Francis Ltd, 2017)
The Pantanal is under the influence of the Paraguay River flood regime is considered to be one of the largest wetlands of the world, and has rich biodiversity, including fishes. Until now, the identification of fish species in this biome has only considered the morphological characteristics of individuals, and the present work aimed to identify the fish species of the Pantanal region through the DNA barcode methodology for investigating the biodiversity in this region. The genetic analysis of 638 samples via the GMYC approach identified 137 operational taxonomic units (OTUs) belonging to 127 species that have previously been described according to their morphological characteristics. Data suggest that 10 cases of morphospecies (Eigenmannia trileneata, E. virescens, Pimelodella gracilis, Brachyhypopomus pinnicaudatus, Brachyhypopomus sp., Ancistrus sp., Hyphessobrycon eques, Jupiaba acanthogaster, and Serrapinnus calliurus) represent complexes of cryptic species, and the number of species described in the Pantanal region has thus potentially been underestimated.
Keywords: Cryptic species; cytochrome oxidase; DNA sequencing; molecular identification; sympatric